The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s10508-016-0758-7
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Mass Index and Physical Activity With Sexual Dysfunction in Breast Cancer Survivors

Abstract: Sexual dysfunction is a common and distressing consequence of breast cancer (BC) treatment. In the present study, we investigated the sexual functioning of BC patients and its association with women's personal characteristics and cancer treatments. In this cross-sectional study, sexual function was assessed using the Female Sexual Function Index (FSFI). The health-related quality of life (HRQOL) was measured using the European Organization for Research and Treatment of Cancer (EORTC) QLQ-C30 and its breast mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Results from a pilot study randomizing BCSs with menopausal symptoms to a lifestyle program including physical activity or standard care support this statement, demonstrating clinically significant reduction in both menopausal symptoms and sexual dysfunction in the intervention group [52]. Another study, exploring the associations of BMI, physical activity, and sexual dysfunction in BCSs, found that regular physical activity was associated with better sexual desire [53]. Further, physical activity may alleviate symptoms of depression [54], fatigue [55], and sleep problems [56], with the potential of indirectly improving sexual functioning.…”
Section: Discussionmentioning
confidence: 91%
“…Results from a pilot study randomizing BCSs with menopausal symptoms to a lifestyle program including physical activity or standard care support this statement, demonstrating clinically significant reduction in both menopausal symptoms and sexual dysfunction in the intervention group [52]. Another study, exploring the associations of BMI, physical activity, and sexual dysfunction in BCSs, found that regular physical activity was associated with better sexual desire [53]. Further, physical activity may alleviate symptoms of depression [54], fatigue [55], and sleep problems [56], with the potential of indirectly improving sexual functioning.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have evaluated the prevalence of SD among BCSs [14][15][16][17][18][19][20][21][22][23][24], but inconsistency in the definition and assessment of SD complicates interpretation and comparison of results.…”
Section: Introductionmentioning
confidence: 99%
“…However, FSFI does not account for distress and only few studies evaluating SD among BCSs have used an additional scale to integrate distress in their definition of SD [15,17,20,31]. Hence, prevalence estimates of SD among BCSs assessed by the FSFI show a considerable variation between studies, ranging from 32% to 93% [14][15][16][17][18][19][20][21]32]. These variations may also reflect differences in age and degree of sexual activity between cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Paiva et al showed the negative correlation between BMI and sexual function. [25] However, in a recent study, it is mentioned that there is no statistically significant correlation between FSFI scores and BMI. [26] In the present study, the BMI of BCS and MRM patients were similar.…”
Section: Discussionmentioning
confidence: 94%